Monumental in Sponsoring. (Bornem : Foundation Helan-Arts vzw, 1991)
Bjarnason, Petur ; Coeckelberghs, Luc ; De Bruyckere, Berlinde ; De Cauter, Wim ; Desmet, Etienne ; Dieltjens, Ann ; Dusépulchre, Francis ; Feidler, Francis ; Ferreo, Constantine ; Machiels, Paul ; Moffarts, Michel ; Saudoyez, Jean-Claude ; Sweetlove, William ; Van Impe, Peter ; Van Soom, Luk ; Verjans, Raf ; Verstockt, Marc ; Wibin, Gérard
21 delen in map
boek